2013
DOI: 10.2174/1745017901309010180
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Transcranial Magnetic Stimulation (rTMS) to Treat Social Anxiety Disorder: Case Reports and a Review of the Literature

Abstract: Objectives: Social anxiety disorder (SAD) is a common and debilitating anxiety disorders. However, few studies had been dedicated to the neurobiology underlying SAD until the last decade. Rates of non-responders to standard methods of treatment remain unsatisfactorily high of approximately 25%, including SAD. Advances in our understanding of SAD could lead to new treatment strategies. A potential non invasive therapeutic option is repetitive transcranial magnetic stimulation (rTMS). Thus, we reported two cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 71 publications
0
21
0
3
Order By: Relevance
“…As medial prefrontal cortex is the most consistent zone of brain in anxiety processing, it was targeted in the therapy 54). In this case study, it was found that low frequency rTMS and high frequency rTMS targeting the right and left medial prefrontal cortex respectively for four weeks was effective in the treatment of social anxiety disorder 54)…”
Section: Brain Stimulation Treatment Of Anxiety Disordermentioning
confidence: 87%
See 1 more Smart Citation
“…As medial prefrontal cortex is the most consistent zone of brain in anxiety processing, it was targeted in the therapy 54). In this case study, it was found that low frequency rTMS and high frequency rTMS targeting the right and left medial prefrontal cortex respectively for four weeks was effective in the treatment of social anxiety disorder 54)…”
Section: Brain Stimulation Treatment Of Anxiety Disordermentioning
confidence: 87%
“…The effectiveness of rTMS in social anxiety disorder was limited to case studies 54). As medial prefrontal cortex is the most consistent zone of brain in anxiety processing, it was targeted in the therapy 54).…”
Section: Brain Stimulation Treatment Of Anxiety Disordermentioning
confidence: 99%
“…Eine Pubmed-Recherche zur sozialen Angststörung (SAD) (keywords: rTMS/ TBS AND social anxiety disorder) führte zu elf Treffern, darunter jedoch keine placebokontrollierten Studien zur SAD. Paes et al identifizierten in einer systematischen Literaturrecherche ebenfalls keine Studien zur rTMS bei SAD, berichten aber drei eigene Therapieversuche, in denen sie jeweils eine Verbesserung der sozial ängstlichen Symptomatik nach 1-Hz-Stimulation über dem ventromedialen DLPFC beobachteten (ein Patient erhielt nur eine Applikation, zwei Patienten erhielten jeweils zwölf Applikationen) (19). Zusammenfassend ist keine Bewertung von rTMS bei GAD und SAD möglich, eine weitere Untersuchung dieser Krankheitsbilder erscheint aber lohnenswert.…”
Section: Ergebnisse Posttraumatische Belastungsstörungunclassified
“…Warto wspomnieć, że stwierdzono także efektywność rTMS w innych zaburzeniach lękowych, takich jak fobie społeczne [42], zaburzenia obsesyjno-kompulsyjne [43], zaburzenia dysocjacyjne [44], zaburzenia stresowe pourazowe [45]. Wskazywano także na poprawę w zakresie objawów depresyjnych współwystępujących z objawami GAD czy lęku panicznego [46,47].…”
unclassified
“…Zasadnicze znaczenie dla rozwoju terapii przy użyciu rTMS będzie miał postęp wiedzy w zakresie neurobiologii i rozwój techniczny. It is worth mentioning that efficacy of rTMS was identified in other anxiety disorders, such as social phobias [42], obsessive-compulsive disorder [43], dissociative disorders [44] and post-stress anxiety disorder [45]. Improvement in depressive symptoms co-existing with GAD symptoms or panic disorder [46,47] was also found.…”
mentioning
confidence: 99%